Process Control and Smart Manufacturing for Industry 4.0 - Yurish, Sergey Y. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint, entitled "Process Control and Smart Manufacturing for Industry 4.0", contains the extended papers from the Series of annual IFSA conferences on Automation, Robotics and Communications for Industry 4.0/5.0 (ARCI) on the following topics: Process Automation, Process Control and Monitoring, Design Principles in Industry 4.0, Smart Manufacturing and Technologies, Smart Factories, Machine Learning and Artificial Intelligence in Manufacturing. The reprint contains 13 chapters written by 54 ARCI conference participants from seven countries: China, Croatia, Denmark, Germany, Italy, Poland and Romania. This reprint will inform readers of cutting-edge developments in the field and provide effective starting points and a road map for further research and development. All chapters follow the same structure: firstly, an introduction to the specific topic under study; secondly, a description of the field, including sensing or/and measuring applications. Each chapter ends with a curated list of references, including books, journals, conference proceedings and websites. "Process Control and Smart Manufacturing for Industry 4.0" is intended for researchers and scientists from academia and industry, as well as for postgraduate students.